2017
DOI: 10.5999/aps.2017.44.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up Study of Young Adults Treated for Unilateral Complete Cleft Lip, Alveolus, and Palate by a Treatment Protocol Including Two-Stage Palatoplasty: Speech Outcomes

Abstract: BackgroundNo consensus exists on the optimal treatment protocol for orofacial clefts or the optimal timing of cleft palate closure. This study investigated factors influencing speech outcomes after two-stage palate repair in adults with a non-syndromal complete unilateral cleft lip and palate (UCLP).MethodsThis was a retrospective analysis of adult patients with a UCLP who underwent two-stage palate closure and were treated at our tertiary cleft centre. Patients ≥17 years of age were invited for a final speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…In these patients, surgical intervention is considered to be the optimal treatment. Because the timing of surgery is generally considered to be an important factor that determines speech outcomes, children who received early surgical intervention had better outcomes [11][12][13][14]. Several studies have suggested that a younger age leads to better results of surgery in children with SMCP, but research on the different effects of treatment depending on the timing of surgery remains insufficient.…”
Section: Clinical Interventions and Speech Outcomes For Individuals Wmentioning
confidence: 99%
“…In these patients, surgical intervention is considered to be the optimal treatment. Because the timing of surgery is generally considered to be an important factor that determines speech outcomes, children who received early surgical intervention had better outcomes [11][12][13][14]. Several studies have suggested that a younger age leads to better results of surgery in children with SMCP, but research on the different effects of treatment depending on the timing of surgery remains insufficient.…”
Section: Clinical Interventions and Speech Outcomes For Individuals Wmentioning
confidence: 99%
“…The previously discussed study by Liao et al (2010), although finding restricted maxillary growth in single-stage patients, also reported a velopharyngeal function level of “adequate” in 48% of single-stage patients, as compared to 22% of 2-stage repair. Several small studies reported increased levels of hypernasality and nasal emission among patients with 2-stage CP (Pradel et al, 2009; Kappen et al, 2017). One reported the 2-stage group experiences a pharyngoplasty rate of 42% (Kappen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most eligible studies (91.3%) were published in the past 2 decades 4,6,7,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Table 2). Most studies were conducted in Europe (43.5%) and 26.2% were conducted in the United States.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…38,39 According to the literature, approximately 50% of patients born with CP develop problems with speech at 3 years of age, even if they underwent palatoplasty. 20,40 Eleven studies (10 retrospective cohort studies 12,14,23-27,30-32 and 1 prospective cohort study 16 ) examined the association between speech and palatal closure technique (Table 6). Dissaux et al 30 compared the VWK straight-line palatoplasty with the Sommerlad IVVP.…”
Section: Speechmentioning
confidence: 99%